A TRAJETÓRIA DO PROJETO DEMOCRÁTICO-PARTICIPATIVO E SEUS IMPACTOS NA ORGANIZAÇÃO DOS MOVIMENTOS POPULARES DO MUNICÍPIO DE CARIACICA/ES (2005/2020). - Ferreira, Gabriela Gilles (2021)
This work aimed to investigate the trajectory of the Democratic-Participative Project (PDP) and its impacts on the organization of Popular Movements in the Municipality of Cariacica / ES between 2005/2020. The most important expression of the PDP was the Participatory Budget (OP), which in the case of the Municipality of Cariacica was implemented in 2005 during the term of ex-mayor Helder Ignácio Salomão - Partido dos Trabalhadores (PT) and continued in the administration of mayor Geraldo Luzia Junior - Popular Citizenship / Citizenship Party. The PDP was one of the elements that materialized the Democratic-Popular Strategy (EDP), developed between the 1990s and 2000 and historically linked to the management of the democratic and popular field, mainly to the PT. The OP was perceived as a trademark of the PT Way of Governing (MPG) and required participation to discuss the destination of resources and public social policies, which especially mobilized associations of residents and entities representing the popular movement, whose trajectories we have outlined in the present work - focusing on the periods from 2005 to 2012 and, subsequently, from the political-party alternation that occurred between 2013-2020. We identified the main strategies for articulating and making feasible demands with the municipal government, seeking to understand the continuities and changes in the engagement, mobilization and organization of popular movements in Cariacica from the participatory experience.